If it's not what You are looking for type in the equation solver your own equation and let us solve it.
30+3(x-4)=6x
We move all terms to the left:
30+3(x-4)-(6x)=0
We add all the numbers together, and all the variables
-6x+3(x-4)+30=0
We multiply parentheses
-6x+3x-12+30=0
We add all the numbers together, and all the variables
-3x+18=0
We move all terms containing x to the left, all other terms to the right
-3x=-18
x=-18/-3
x=+6
| (5(x-3)/2-1=14 | | 3(y-2)=-2(-2y+6) | | 3y-7+y+33=7y+30-5y | | 9m-4=8+5m | | 3.5x+10=5.25 | | 5.5z-19.72-19.8z=18.68-4.7z | | |3x-1|+6=4x | | 4n-3(n-2)=6n-4 | | 3r-7=3r-2 | | −2x=3x+10 | | 5=2h+6 | | 6=9p | | 14-1/5(20u+5)=-5u-9 | | x3+9=18 | | 21h+21=27 | | 29x-1+26x+3=167 | | 6x=30+3(x–4) | | -8(-8k-6)=-6k-32 | | 12x+450=11x+950 | | (X)=90+3(x-5) | | 3x+15=52.50 | | y=2^2-12 | | -996,010=17001700-55g | | 1/6x-3/4=1/2 | | 6=p9 | | d/4−1=3 | | 4c5+∣−6=−5 | | 5x-7(3-2x)=-36 | | 2x-4(x-5)=3+5x-33 | | 5=(-8+3x)/(2) | | -7-4b=-5b | | 19=j/4+16 |